The linguistic issue in Africa in light of.the features of the colonial linguistic policyAlgeria is a model. (مجلة إحالات, 2026)
Alarm, which calls for speeding up papers and reading the linguistic reality with the right eyesin order to find solutions to contain it. the crisis. This paper comes mainly after extrapolating thelinguistic situation in Africa and Algeria specifically to stand for the colonial linguistic exchange todemolish the official language, and broaden the picture between the originalLanguage and the speakers. And standing on the same compatibility with alternative programsto the current situation in Latin America, and resorting to systems and languages in Algeria as needed.Each language preserves its identity and protects the nation from linguistic fragmentation anddisruption